Peningkatan Kemampuan Berbahasa Anak Kelompok B Melalui Metode Bercerita Di BA ‘Aisyiyah Beku Klaten - Nurahmawati, Nurahmawati; Khotimah, Ihda A'yunil; Fauzi, M. Rofi (Institut Agama Islam Negeri Metro, 2023)
This study aims to determine the application of the Storytelling Method in improving language development in children and to determine the increase in children's language development after using the Storytelling Method in group B at BA 'Aisyiyah Beku, Karanganom, Klaten. The method used in this research is Classroom Action Research (CAR), with 4 research steps namely planning, implementation, observation and reflection. Data collection techniques used in this study are observation and documentation. The results of this study are that first the application of storytelling is carried out with the stages of child conditioning, children are asked to pay attention to stories with the theme of natural disasters. To find out the child's courage, the teacher asks the child to appear in front of the class and answer the teacher's questions about the contents of the story. To find out the fluency of the child's language, the teacher gives the task to the child to say simple sentences of 4-6 words fluently and in retelling, the teacher gives the opportunity for the child to retell the story. Second, improving language skills after being given the action of using the storytelling method can improve children's language skills in group B at BA Aisyiyah Frozen. This can be seen from before the action or initial conditions of 32.03%. Cycle I increased language skills 64.06%. Cycle II increased language skills 85.93%. So from the Pre-Cycle action to cycle II there was an increase of 53.9%.